ASSESSING THE MEAN HEIGHT OF SCHOOL GOING CHILDREN IN REASI DISTRICT, JAMMU & KASHMIR: A COMPARISON WITH WHO AND ICMR STANDARDS - Nawaz, Ashraf; Saluja, Rajni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study assesses the mean height of school-going children in the Reasi district of Jammu & Kashmir, comparing the findings with WHO and ICMR reference standards. A total of 400 children (219 boys and 181 girls) aged 6 to 10 years were included in the analysis. The results revealed that the mean heights of both boys and girls were consistently lower than the reference standards, with girls exhibiting larger deviations than boys. The largest differences from WHO standards were observed at age 10 for boys and at age 7 for girls. In comparison, the deviations from ICMR standards were slightly smaller but still significant. The study highlights the challenges faced by children in this region, where malnutrition, socio-economic disparities, and limited access to healthcare contribute to stunted growth. The findings underscore the need for targeted interventions to address these issues and promote optimal growth among children in rural areas.